سردية الخطاب وسردية الصورة عند رولان بارت قراءة المعنى وآليات التأويل - بن زهية, عبد الله (قــــــراءات, 2019)
يتناول هذا المقال دراسة تحليلية للأليات التي اعتمدها رولان بارت في إعطاء منهج جديد لقراءة الصورة على تعدد أشكالها بالمقارنة مع النص المكتوب، والتي قدم من خلالها تصورا متفردا تعريفا ووظيفة من خلال الغوص فيها باعتبارها لغة تشتمل على علامات ودلالات لها جذورها الاجتماعية والإيديولوجية فقد اعتبرها نصا  تشكل من عناصر منتقاة وفق عوامل جمالية و أخرى إيديولوجية، وهو ما جعلها نصا يتيح للقارئ رؤية المعنى على حسب ما تمكنه خلفيته الثقافية والتاريخية من جهة، وذوقه الفني من جهة أخرى، ففي هذا البحث سنحاول معرفة الأليات الإجرائية التي تبناها رولان بارت للكشف عن المعاني والخلفيات الكامنة وراء النصوص، والكشف عن الروح التي تسكنها.   Summary : This article deals with an analytical study of the mechanisms adopted by Roland Barthes to give a new approach to read the image on the multiplicity of forms, compared with written text that presents the vision of a unique definition and function through diving in as a language which includes signs and indications of a social and ideological roots. it was considered as text formed of selected elements in accordance with the aesthetic and other ideological factors which allow the reader to see the meaning according to his cultural and historical background on one hand and artistic taste on the other hand. In this research,we will try to find out the procedural mechanisms adopted by Roland Barthes to reveal the meanings and backgrounds behind the texts, and the disclosure of the spirit that inhabited them.